Analyzing Lexus of Edmonton's Marketing Channels - Lauer, Camryn; Yaremovich, Hannah; Giasson, Kara; Januszczak, Julia; Checknita, Sydney (MacEwan University Student eJournal, 2025)
This report was conducted for Lexus of Edmonton to identify the best social media platform to invest their marketing budget in order to obtain the best ROI. We analyzed individuals' social media usage from various age groups of both current and potential clients to determine whether Facebook, Instagram, Youtube, or TikTok was the most effective in generating sales leads. By investigating how dealerships can market themselves in social media through conveying experiences and emotion with targeted content, we conducted a survey using simple random sampling (SRS) with 103 respondents to answer the management objective and determine the accuracy of our hypotheses.